Encruza: Yorùbá metaphysics as an epistemology of black-Brazilian dance (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
This article investigates the possibilities of thinking about the aesthetics of a black-Brazilian dance, based on Afrodiasporic philosophies and the epistemologies of myth, body and ancestry, a path towards the cosmoperception of scenic processes in the spectacularity of black art - a case study anchored in the assembly of the dance show ENCRUZA. In this way, we present images, propositions and records of the possible paths of the Afrodiasporic pantheon adopted in choreographic processes. Reflections between body, life, spectacularity and Yorùbá metaphysics that reverberate in the propositions of scenic-ontological strongholds that collaborate in the gestural construction of the artist.
Keywords: reduto; body; black-Brazilian dance; afrodiasporic philosophies